Respuesta :

Answer: x= −5

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

4−2(x+7)=3(x+5)

4 + (−2)(x)+(−2)(7) = (3)(x)+ (3)(5) (Distribute)

4+−2x + −14= 3x+ 15

(−2x)+(4+−14)=3x+15(Combine Like Terms)

−2x + −10= 3x+15

−2x−10=3x+15

Step 2: Subtract 3x from both sides.

−2x−10−3x=3x+15−3x

−5x−10=15

Step 3: Add 10 to both sides.

−5x−10+10=15+10

−5x=25

Step 4: Divide both sides by -5.

−5x/−5 = 25/−5

x=−5

*Hopefully this helps:) mark me the brainliest:)!!!

Answer:

x=-5

Step-by-step explanation:

4-2(x+7) = 3(x+5)

distribute:

4-2x-14=3x+15

combine like terms:

-10-2x=3x+15

subtract 3x from both sides:

-10-5x=15

ADD 10 from both sides to cancel out -10:

-5x=25

Divide -5 from both sides to cancel out the variable:

Answer: x=-5